KONFLIK HUKUM UNDANG-UNDANG RI NOMOR 19 TAHUN 2002 TENTANG HAK CIPTA DENGAN HAK-HAK MASYARAKAT ADAT DI INDONESIA - Asma Karim (IAIN Ambon, 2017)
This article discusses the law conflict of Act RI No. 19, 2002 on Copyright with the traditional community rights in Indonesia. This study used a normative juridical method. Based on a normative study can be recognized: First the Act No. 19, 2002 lead to the law conflicts because of the formulation of Article 10 of this Act only authorizes the head of state as the Folklore holder (Folklore: part of the Traditional Knowledge) but the community rights as the owner of Traditional Knowledge and the Folklore itself was not accommodated in this Act, so that its existence was marginalized. Secondly, the differences in paradigms on the ownership concept between the customary law and Western law in the protection of intellectual property rights lead to many deviations that adverse the traditional community rights themselves. Keywords: Law Conflict, Act on Copyright with the Traditional Community rights